A New Glaucoma Severity Score Combining Structural and Functional Defects - Wachtl, J.; Töteberg-Harms, M.; Frimmel, S.; Kniestedt, C. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background In order to assess glaucoma severity and to compare the success of surgical and medical therapy and study outcomes, an objective and independent staging tool is necessary. A combination of information from both structural and functional testing is probably the best approach to stage glaucomatous damage. There has been no universally accepted standard for glaucoma staging. The aim of this study was to develop a Glaucoma Severity Score (GSS) for objective assessment of a patientʼs glaucoma severity, combining both functional and structural information. Materials and methods The Glaucoma Severity Score includes the following 3 criteria: superior and inferior Retinal Nerve Fibre Layer (RNFL) thickness, perimetric mean defect (MD), and agreement of anatomical and perimetric defects, as assessed by two glaucoma specialists. The specialists defined a staging tool for each of the 3 criteria in a consensus process, assigning specific characteristics to a scale value between 0 and 2 or 0 and 3, respectively. The GSS ranges between 0 and 10 points. In a prospective observational study, the data of 112 glaucoma patients were assessed independently by the two specialists according to this staging tool. Results The GSS was applied to 112 eyes and patients (59.8 % female) with a mean age of 66.3 ± 13.1 years. Mean GSS was 4.73 points. Cohenʼs kappa coefficient was determined to measure inter-rater agreement between glaucoma specialists for the third criterion. With κ = 0.83, the agreement was very good. Thus, all 3 criteria of the GSS may be regarded as objective. Conclusions The Glaucoma Severity Score is an objective tool, combining both structural and functional characteristics, and permitting comparison of different patients, populations and studies. The Glaucoma Severity Score has proven effective in the objective assessment of 112 glaucoma patients and is relatively user-friendly in clinical practice. A comparative study of the GSS with the results of the FORUM® Glaucoma Workplace (Carl Zeiss Meditec AG, Jena, Germany) will be the next step. If outcomes match, the Glaucoma Severity Score can be accepted as a promising tool to stage glaucoma and monitor changes objectively in patients when comparing glaucoma progression in study analyses.
Keywords: glaucoma; glaucoma staging system; score; retinal nerve fibre layer